Achieving a framework of the circular economy in urban transport infrastructure projects: a meso-scale perspective - Liu, Xinyu; Schraven, Daan; Ma, Wenting; de Jong, Martin; Hertogh, Marcel (Frontiers in Sustainability, 2024)
Urban infrastructure development is one principal way people are transforming the natural world and their living conditions. It is important for humanity, but it can also cause major impacts to the environment, such as huge amounts of solid waste and CO2 emissions. Considering this, the Circular Economy (CE) is a promising alternative to the traditional "make, use, and dispose" linear economy model. However, as a strategy for sustainable development (SD), the CE is still in its infancy in the urban transport infrastructure sector. Therefore, this article aims to guide the implementation of CE during transport infrastructure projects. To achieve this goal, literature review and case study were adopted as the research methods. After reviewing existing well-established CE frameworks, the iReSOLVE (implement, Regenerate, Share, Optimize, Loop, Virtualize, Exchange) framework is recognized as the most comprehensive one. Upon it, an analytical framework containing specific related aspects of CE in urban transport infrastructure projects (which belongs to meso-scale) is proposed (coined as the 4Wh-iReSOLVE framework). The 4Wh means Who, When, Where, and What. The proposed framework offers insight into potential CE activities for transport infrastructure projects and assists in assessing the performance and impacts of CE of these projects, to cover the gap of the neglected meso-scale. Ten circular viaduct project initiatives in the Netherlands are used as case analyses with the 4Wh-iReSOLVE framework. The results present the highlights of the circular viaduct initiatives in the Netherlands, with CE activities categorized into five groups (Design-related strategies, General CE strategies, Implementation, management and related digital technologies, Materials, as well as Environmental sustainability). As verified by several experts of the projects studied, it can be concluded that the 4Wh-iReSOLVE framework is suitable for transport infrastructure project CE analyses and implementations. It can potentially be a suggested guideline in future policy documents.